Landscape and cultural identity in Spain - Juan José González Trueba (Ибероамериканские тетради, 2017)
The landscape is a complex concept that results from the interplay of nature, society and culture. It`s outlined, ﬁrstly, the geographical ideas, general concepts, perception and interpretation of Spanish landscape. For the ﬁrst time, a new word is proposed for the Spanish language: “maresaje”, to make reference to the marine landscape or seascape. Therefore, this paper aims to highlight the interest of deep and valuable images about landscape and seascape coming from literature and painting for the construction of Spanish cultural identity.